System and method for improving structure discovery and representation learning of multi-subject data - LUCY PATRICK; HARBERS, JENNIFER (2022)
A computing system retrieves player tracking data for a plurality of players across a plurality of events. The player tracking data includes player position coordinates during each event. The computing system initializes player tracking data based on an average location of each player in the plurality of events. The computing system learns an optimal formation of player positions using a Gaussian mixture model based on player tracking data. The computing system aligns the optimal formation of the player location with the global template by identifying a distance between each distribution in the optimal formation and each distribution in the global template to generate a learned formation template. The computing system assigns a character to each player in the learned template. 一种计算系统检索跨多个事件多个选手的选手跟踪数据。选手跟踪数据包括每个事件期间的选手位置坐标。计算系统基于多个事件中每个选手的平均位置来初始化选手跟踪数据。计算系统基于选手跟踪数据使用高斯混合模型来学习选手位置的最佳阵型。计算系统通过识别最佳阵型中的每个分布与全局模板中的每个分布之间的距离来将选手位置的最佳阵型与全局模板对齐，以生成经学习的阵型模板。计算系统为经学习的模板中的每个选手分配一个角色。